The Use of Artificial Intelligence (AI) in PAI Learning to Develop Students' Critical Thinking Skills - Ayu Fitriyatul Hasanah; A. Faizul Mubarak (Yayasan Rahmat Islamiyah, 2026)
The purpose of this study is to analyze how the use of Artificial Intelligence can contribute to the development of critical thinking skills in Islamic religious education (PAI) lerning. This study uses a qualitative descriptive method with a literature review approach through journal artcles, books, and literary works related to the use of Artificial Intelligence (AI) and critical theory. The results of the study indicate that Artificial Intelligence (AI) plays an important role in creating adaptive, interactive, and analytical learning through featuares such as Natural Language Processing. (NLP), adaptive learning, educational chatbots, and data -driven automated evaluation. This technology enables students to critically analyze religious texts, compare references, and evaluate the quality of information to systematically improve their critical thinking skills. In addition, Artificial Intelligence helps teachers personalize materials, provide quick feedback, and enrich classroom discussions using structured data. This study shows that the use of Artificial Intelligence (AI) is not only a technical tool, but also a useful educational tool to improve the quality of education in the digital era. This is a summary of the reasons for conducting the research, the approaches or methods chosen, important results, and main conclusions.